Transformasi Tata Kelola Pemerintahan Desa Pancana Melalui Evaluasi Mutu Pelayanan Demi Tercapainya Desa Swasembada - Ulfiah Syukri (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2022)
The government must fulfill the basic needs and rights of civil society through efforts to provide quality public services. Efforts through service quality evaluation are one of the right steps to review the success of each region in providing public services according to applicable rules, especially in small sub-units such as villages. The purpose of this research is to measure the success of Pancana Village services using the benchmark of Permendagri No. 7 of 2017 for the realization of self-sufficient villages. This research uses descriptive qualitative method. The data collection techniques used by the author in this study are library research, field studies consisting of observations and interviews and documentation studies. Data analysis used descriptive analysis techniques, namely to analyze more deeply about the evaluation of service quality in Pancana village through one special indicator, namely Permendgari No.2 of 2017. maximum, every SPM indicator has been met 2) Pancana Village has been categorized as a self-sufficient village in Barru Regency from around 40 villages, not only that the efforts of village government officials to lead Pancana village as a self-sufficient village are realized by making Pancana village a tourist village.